Favorable conditions for epistemic validity in deliberative experiments : A methodological assesment (2012)
Methodological evaluations of deliberative mini-publics usually focus on the internal and external validity of experimental designs. Even though such a focus on causal inference and generalization is important, it is incomplete. We argue that the epistemic validity of experimental designs should also be taken into account in order to ensure measuring truly a deliberative exercise rather than just a regular discussion. By ensuring the inclusion and publicity of all arguments, the process of arguing back-and-forth between multiple positions is theoretically claimed to generate better outcomes and should therefore be validated along epistemic lines. Here, we suggest some methodological techniques for enabling the epistemic validity assumption of deliberative experimental designs. These techniques relate to the sampling of the groups and the treatments they receive.